2016
DOI: 10.9767/bcrec.11.2.540.140-150
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of SrO-MBCUS Agglomerates for Esterification and Transesterification of High FFA Vegetable Oil

Abstract: <p>Musa Balbisiana Colla Underground Stem (MBCUS) catalyst was treated thermally mixing with 5:1 w/w of Strontium Oxide (SrO) and the dynamic sites were reformed. The MBCUS-SrO showed sharper crystalline phases as evidence from XRD and TEM analysis. The composition and morphology were characterized from BET, SEM, EDX thermo-gravimetric analysis (TGA) and XRF analysis. The optimization process for biodiesel production from Jatropha curcas L oil (JCO) having high percentage of free fatty acids was carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 24 publications
2
5
1
Order By: Relevance
“…Chemical activation has been shown to favor the presence of active sites on the catalyst surface, which benefits its catalytic activity. This statement corresponds to the results obtained by Kumar et al 82 The authors used Jatropha curcas oil for biodiesel production using a nano‐sized catalyst Musa Balbisiana Colla underground stem (MBCUS) ash‐based, following the procedure described by Sarma et al 84 Subsequently, SrO was impregnated in a weight ratio of 1:5 (1 g of SrO per 5 g of nanocatalyst). This mixture (MBCUS‐SrO) was heat‐treated for 1 hour at 550°C.…”
Section: Heterogeneous Catalysts Preparation Based On Different Bioma...supporting
confidence: 82%
See 3 more Smart Citations
“…Chemical activation has been shown to favor the presence of active sites on the catalyst surface, which benefits its catalytic activity. This statement corresponds to the results obtained by Kumar et al 82 The authors used Jatropha curcas oil for biodiesel production using a nano‐sized catalyst Musa Balbisiana Colla underground stem (MBCUS) ash‐based, following the procedure described by Sarma et al 84 Subsequently, SrO was impregnated in a weight ratio of 1:5 (1 g of SrO per 5 g of nanocatalyst). This mixture (MBCUS‐SrO) was heat‐treated for 1 hour at 550°C.…”
Section: Heterogeneous Catalysts Preparation Based On Different Bioma...supporting
confidence: 82%
“…This brings about an increase in surface area, and therefore, enhances the activity of the ash-based catalyst. There are reports with similar observations for ash derived from Lemna pepusilla Torrey, 99 coconut husk, 87 banana peels, 31,75,77,78,81,82,102 orange peels, 97,103 wood pellets, 85 Sesamum indicum plant, 90 and Brassica nigra. 96 Sharma et al 35 also reported the importance of applying a calcination process, as it prevents the leaching of K and influences the reusability of the catalyst.…”
Section: Ash-based Solid Catalystssupporting
confidence: 66%
See 2 more Smart Citations
“…Biodiesel yield is 90 % in 20 minutes, and the SrO weakness is still homogeneous, so it is necessary to add a support such as SiO2 [4]. The modification of SrO catalyst is made by formulating SrO with Musa Balbisiana Colla Underground Stem (MBCUS) to form agglomeration [5]. The result is used to synthesize biodiesel oils with a high free fatty acid level through esterification and transesterification reaction.…”
Section: Introductionmentioning
confidence: 99%